2004
DOI: 10.1631/jzus.2004.1413
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear control for a class of hydraulic servo system

Abstract: The dynamics of hydraulic systems are highly nonlinear and the system may be subjected to non-smooth and discontinuous nonlinearities due to directional change of valve opening, friction, etc. Aside from the nonlinear nature of hydraulic dynamics, hydraulic servo systems also have large extent of model uncertainties. To address these challenging issues, a robust state-feedback controller is designed by employing backstepping design technique such that the system output tracks a given signal arbitrarily well, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…A robust state-feedback controller is designed by employing backstepping design technique such that the system output tracks a given signal and all signals in the closedloop system remain bounded [9]. The backstepping design strategy also used to develop a Lyapunov-based nonlinear controller for a hydraulic servo system which incorporates load, hydraulic, and valve dynamics in the design process [10].…”
Section: Introductionmentioning
confidence: 99%
“…A robust state-feedback controller is designed by employing backstepping design technique such that the system output tracks a given signal and all signals in the closedloop system remain bounded [9]. The backstepping design strategy also used to develop a Lyapunov-based nonlinear controller for a hydraulic servo system which incorporates load, hydraulic, and valve dynamics in the design process [10].…”
Section: Introductionmentioning
confidence: 99%
“…It can make the actuator to complete the appropriate actions in accordance with the requirements by controlling the pressure, flow rate and flow direction of working fluid. Hong has summarized the characteristics of the various electro-hydraulic servo systems, and indicated that it can realize complex program control and remote control by using electrical signals as well as has higher control precision by using feedback [1]. At the same time, Li and Ding have studied the position servo control of the electro-hydraulic proportional system.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, FitzSimons and Palazzolo [8] used linear control theory and Vossoughi and Donath [9] utilized feedback linearization in their respective hydraulic control problems. Recently, quantitative feedback theory, in Pachter et al [2] and Niksefat and Sepehri [10], and backstepping design technique (Yu et al, [11]) have been used to create robust controllers. However, it is in Alleyne and Hedrick [3] where nonlinear adaptive control is applied in the presence of parametric uncertainties.…”
Section: Introductionmentioning
confidence: 99%